Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
By using lithium transition metal composite oxide and carbon nanotube in the positive electrode mixture layer of the nonaqueous electrolyte secondary battery, the problem of improving circulation characteristics is solved, high capacity and cycle stability are achieved, and battery charging is significantly improved Discharge performance.
Patent Information
- Application Number
- CN202180078447.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-30
- Filing Date
- 2021-11-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-11-30
AI Technical Summary
The existing nonaqueous electrolyte secondary batteries still have room for improvement in charge and discharge cycle characteristics, especially in terms of taking into account high capacity and good cycle characteristics, and the existing technology is difficult to effectively improve.
The lithium transition metal composite oxide containing the general formula LixNi1-y-zCoyMzO2 and LiaNi2-a-bMebO2 in the positive electrode mixture layer, and carbon nanotubes are used to protect the first lithium transition metal by combining the second lithium transition metal composite oxide. The surface of the composite oxide suppresses deterioration and improves circulation characteristics.
The charge and discharge cycle characteristics of the nonaqueous electrolyte secondary battery are significantly improved, taking into account high capacity and good cycle stability, and the combination of composite oxides and carbon nanotubes is achieved, a more effective protection effect is achieved.
Smart Images

Figure CN116472250B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery using the positive electrode. Background Art
[0002] The non-aqueous electrolyte secondary battery has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and a non-aqueous electrolyte, and has a structure in which these components are stored in an outer casing. The composition of the positive electrode, which is the main component of the non-aqueous electrolyte secondary battery, has a great influence on the battery characteristics including the charge and discharge cycle characteristics, so there have been many studies on the positive electrode. For example, in patent documents 1 and 2, a positive electrode active material for the purpose of improving performance such as charge and discharge cycle characteristics is disclosed.
[0003] The positive electrode active material disclosed in Patent Document 1 is a general formula Li x Ni 1-y-z-v-w Co y Al z M1 v M2 w The composite oxide represented by O2, wherein the element M1 is at least one selected from Mn, Ti, Y, Nb, Mo and W, the element M2 is at least two selected from Mg, Ca, Sr, Ba and Ra, and the element M2 contains at least Mg and Ca.
[0004] In addition, the positive electrode active material disclosed in Patent Document 2 is [L] 3a [M] 3b [O2] 6c The composite oxide represented by (L=Li, M=Ni, Mn, and Co, or Li, Ni, Mn, and Co) contains 0.1 to 5 mol% of one or more elements selected from Mo, W, Nb, Ta and Re relative to the total molar amount of Mn, Ni, and Co.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 4781004
[0008] Patent Document 2: Japanese Patent No. 5359140 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, with the popularization of on-vehicle use, power storage use, etc. of non-aqueous electrolyte secondary batteries, further high performance is required for non-aqueous electrolyte secondary batteries, especially improvement in charge-discharge cycle characteristics. There is still room for improvement in the prior art including the technologies of Patent Documents 1 and 2 for improving cycle characteristics.
[0011] Means for Solving the Problem
[0012] The positive electrode for a non-aqueous electrolyte secondary battery of the present invention is characterized in that, in a positive electrode for a non-aqueous electrolyte secondary battery having a positive electrode mixture layer, the positive electrode mixture layer contains a first lithium transition metal composite oxide represented by the general formula Li x Ni 1-y-z Co y M z O2 (wherein 0.8 ≤ x ≤ 1.2, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.5, and M is at least one metal element other than Li, Ni, and Co), a second lithium transition metal composite oxide represented by the general formula Li a Ni 2-a-b Me b O2 (wherein 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, and Me is at least one metal element other than Li and Ni), and carbon nanotubes.
[0013] The non-aqueous electrolyte secondary battery of the present invention includes the above positive electrode, negative electrode, and non-aqueous electrolyte.
[0014] Effects of the Invention
[0015] According to the positive electrode of the present invention, the charge-discharge cycle characteristics of a non-aqueous electrolyte secondary battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 FIG. is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an embodiment.
[0017] Figure 2 FIG. is a view showing an enlarged part of a cross-section of an electrode body as an example of an embodiment. DETAILED DESCRIPTION OF THE INVENTION
[0018] As described above, improving charge-discharge cycle characteristics is an important subject in non-aqueous electrolyte secondary batteries. In particular, it is desired to achieve both high capacity and good cycle characteristics of the battery. The present inventors conducted in-depth research on the improvement of cycle characteristics, and as a result, found that by using a first lithium transition metal composite oxide represented by the general formula Li x Ni 1-y-z Co y M z O2, a second lithium transition metal composite oxide represented by the general formula Li a Ni 2-a-b Me bThe second lithium transition metal composite oxide represented by O2 and the positive electrode of carbon nanotubes specifically improve the cycle characteristics of the battery.
[0019] The mechanism of improving the cycle characteristics by using the first lithium transition metal composite oxide, the second lithium transition metal composite oxide and the carbon nanotubes in combination is not clear, but it is believed that the second lithium transition metal composite oxide protects the surface of the first lithium transition metal composite oxide to suppress degradation. Furthermore, it is believed that the protective effect is more effectively exerted by the contact between the composite oxide particles via the carbon nanotubes, and as a result, the cycle characteristics are greatly improved.
[0020] In addition, the first lithium transition metal composite oxide has Ni as an essential component, and by increasing the Ni content, it becomes easier to achieve both high capacity and good cycle characteristics. The effect of adding the second lithium transition metal composite oxide is more effective when using the first lithium transition metal composite oxide with a high Ni content.
[0021] Hereinafter, an embodiment of a positive electrode and a nonaqueous electrolyte secondary battery using the positive electrode according to the present invention will be described in detail with reference to the accompanying drawings. It should be noted that a combination of a plurality of embodiments and modifications described below is also included in the present invention.
[0022] In the following, a cylindrical battery in which a wound electrode body 14 is housed in a bottomed cylindrical outer can 16 is exemplified, but the outer can of the battery is not limited to a cylindrical outer can, and may be, for example, a square outer can (square battery), a coin-shaped outer can (coin-shaped battery), or an outer can composed of a laminated sheet containing a metal layer and a resin layer (laminated battery). In addition, the electrode body may also be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated via a separator.
[0023] Figure 1 Schematic diagram of a cross section of a non-aqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with an opening on one side in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. For the sake of convenience in the following description, the sealing body 17 side of the battery is taken as the upper side, and the bottom side of the outer can 16 is taken as the lower side.
[0024] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. In other words, the negative electrode 12 is formed to be longer in the long side direction and the width direction (short side direction) than the positive electrode 11. The separator 13 is formed to be at least one circle larger than the positive electrode 11, and two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0025] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0026] As described above, the outer can 16 is a metal container in the shape of a bottom cylinder with one side open in the axial direction. A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness of the battery interior and the insulation between the outer can 16 and the sealing body 17. A groove portion 22 is formed on the outer can 16 to support the sealing body 17 by protruding a part of the side portion inward. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the open end of the outer can 16 riveted to the sealing body 17.
[0027] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover body 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When an abnormality occurs in the battery and the internal pressure rises, the lower valve body 24 is deformed and ruptured in a manner that presses the upper valve body 26 toward the cover body 27 side, thereby cutting off the current flow path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 ruptures and gas is discharged from the opening of the cover body 27.
[0028] The following is a reference to Figure 2The positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte constituting the non-aqueous electrolyte secondary battery 10 will be described in detail. Figure 2 It is a schematic diagram showing an enlarged part of the cross-section of the electrode body 14.
[0029] <Positive electrode>
[0030] As Figure 2 shown, the positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 formed on at least one surface of the positive electrode core 30. The positive electrode core 30 can use foils of metals such as aluminum and aluminum alloys that are stable within the potential range of the positive electrode 11, as well as thin films with such metals disposed on the surface layer. It is preferable that the positive electrode mixture layer 31 is formed on both sides of the positive electrode core 30 and contains a positive electrode active material, a conductive agent, and a binder. A lithium transition metal composite oxide can be used as the positive electrode active material. The positive electrode 11 can be manufactured by coating a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder on the positive electrode core 30, drying the coating film and then compressing it to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.
[0031] Examples of the binder contained in the positive electrode mixture layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resins, and polyolefins. In addition, these resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, and polyethylene oxide (PEO). The content of the binder is, for example, 0.1 to 5% by mass, or 0.5 to 3% by mass, relative to the total mass of the positive electrode mixture layer 31.
[0032] The positive electrode mixture layer 31 contains at least two kinds of lithium transition metal composite oxides. The first lithium transition metal composite oxide (hereinafter referred to as "composite oxide (A)") is a composite oxide represented by the general formula Li x Ni 1-y-z Co y M z O2 (where 0.8 ≤ x ≤ 1.2, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.5, and M is at least one metal element other than Li, Ni, and Co). The second lithium transition metal composite oxide (hereinafter referred to as "composite oxide (B)") is a composite oxide represented by the general formula Li a Ni 2-a-b Me b O2 (where 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, and Me is at least one metal element other than Li and Ni).
[0033] In the positive electrode mixture layer 31, the charge and discharge cycle characteristics are specifically improved by the coexistence of the composite oxide (A, B). It is believed that the composite oxide (B) protects the particle surface of the composite oxide (A), effectively suppresses the degradation of the particle surface, and as a result, greatly improves the cycle characteristics. In particular, when the particles of the composite oxide (A, B) are in contact with each other or through carbon nanotubes (CNTs), the protective effect works more effectively. In addition, the composite oxide (B) can be subjected to a strong shear force, a compressive force, and mixed with the composite oxide (A), and immobilized on the surface of the composite oxide (A).
[0034] The above-mentioned effect is achieved by adding a small amount of composite oxide (B), but in order to maintain a high battery capacity and improve the cycle characteristics, there is a preferred range for the addition amount of composite oxide (B). Relative to the total mass of the positive electrode mixture layer 31, the content of composite oxide (B) is preferably 0.05 to 10% by mass, more preferably 0.1 to 7% by mass, or 0.1 to 5% by mass. Similarly, relative to the total mass of the positive electrode active material, it is preferably 0.05 to 10% by mass, more preferably 0.1 to 7% by mass, or 0.1 to 5% by mass. When the amount of composite oxide (B) is within this range, the cycle characteristics can be effectively improved.
[0035] The positive electrode mixture layer 31 may contain a composite oxide other than the composite oxide (A, B) (for example, a lithium transition metal composite oxide that does not satisfy the above general formula) within a range that does not impair the purpose of the present invention. The composite oxide (A, B) is preferably contained in an amount of 50% by mass or more relative to the total mass of the positive electrode mixture layer 31. The total content of the composite oxide (A, B) relative to the total mass of the positive electrode mixture layer 31 is, for example, 85% by mass or more, or 90% by mass or more, or 95% by mass or more. An example of a suitable content is 90 to 99% by mass, or 95 to 99% by mass.
[0036] [First lithium transition metal composite oxide (composite oxide (A))]
[0037] The composite oxide (A) is a composite oxide represented by the above general formula, and contains at least one metal element M other than Li, Ni and Co as an essential constituent element. In addition, the composite oxide (A) preferably contains Co. However, Co is particularly rare and expensive, so the composite oxide (A) may not contain Co substantially. When the composite oxide (A) contains Co, the content of Co is 20 mol% or less, more preferably 0.1 to 10 mol%, or 0.5 to 5 mol%, relative to the total molar amount of the metal elements other than Li. It should be noted that the molar fraction of the metal element in the composite oxide can be measured by inductively coupled plasma (ICP) emission spectrometry.
[0038] For the composite oxide (A), among the metal elements other than Li, the content of Ni is preferably the largest. Relative to the total molar amount of the metal elements other than Li, the content of Ni is preferably 50 mol% or more, more preferably 70 mol% or more, and particularly preferably 80 mol% or more. A suitable example of the Ni content is 80 to 97 mol%, or 85 to 95 mol%. That is, a suitable example of (1-yz) representing the Ni content in the above general formula is 0.80≤(1-yz)≤0.97, or 0.85≤(1-yz)≤0.95.
[0039] As described above, a suitable example of the composite oxide (A) is a composite oxide containing more than 80 mol% of Ni relative to the total molar amount of metal elements other than Li. By increasing the proportion of Ni in the metal elements in the composite oxide (A), the high capacity of the battery can be sought. In addition, the Ni-rich composite oxide (A) has good compatibility with the composite oxide (B), which is effective from the perspective of improving cycle characteristics. In the above general formula, x representing the Li content is 0.8≤x≤1.2, or 0.97≤x≤1.2, and the composite oxide (A) can be a lithium-excess composite oxide in which the molar ratio of Li to the transition metal exceeds 1.
[0040] The composite oxide (A) contains at least one metal element M other than Li, Ni and Co. The metal element M is, for example, at least one selected from Mn, W, Mg, Mo, Nb, Ti, Si, Al, Zr, B, Fe, Cu, Zn, Sn, Na, K, Ba, Sr and Ca, and more preferably at least one selected from Mn, W, Mg, Mo, Nb, Ti, Si, Sr, Ca and Al. Among them, it is preferred to contain at least one of Mn and Al. The content of the metal element M is the total when there are multiple elements, and is 50 mol% or less relative to the total molar amount of the metal elements other than Li, and more preferably 0.1 to 20 mol%, or 0.5 to 10 mol%, or 1 to 5 mol%.
[0041] The composite oxide (A) has, for example, a crystal structure belonging to the space group R3-m. Furthermore, the composite oxide (A) has a layered structure including a transition metal layer, a Li layer, and an oxygen layer. In this case, the protective effect of the composite oxide (B) is more effectively exerted, and a stable crystal structure can be maintained even after repeated charge and discharge, which can more effectively improve the cycle characteristics. In addition, the BET specific surface area of the composite oxide (A) is, for example, 0.2 to 2.0 m 2 The BET specific surface area was measured according to the BET method (nitrogen adsorption method) described in JIS R1626.
[0042] The composite oxide (A) is, for example, a secondary particle formed by the aggregation of multiple primary particles. An example of the volume-based median particle size (D50) of the composite oxide (A) is 3 to 20 μm, or 5 to 15 μm. D50 refers to the particle size at which the frequency accumulates to 50% from the smallest particle size in the volume-based particle size distribution, also known as the median diameter. The particle size distribution of the secondary particles of the composite oxide can be measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by MicrotracBEL) with water as the dispersion medium. The particle size of the primary particles of the composite oxide (A) is, for example, 0.05 μm to 1 μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the cross-sectional image of the secondary particles observed by a scanning electron microscope (SEM).
[0043] In addition, a compound containing at least one selected from Sr, Ca, W, Mg, Nb, and Al (hereinafter referred to as "metal element M2") may be fixed to the particle surface of the composite oxide (A). The M2 compound containing the metal element M2 may exist in a point-like manner on the particle surface of the composite oxide (A), or may exist in a layered manner covering the entire surface of the particle. The thickness of the layer of the M2 compound is, for example, 0.1 to 5 nm. It is believed that the M2 compound protects the surface of the composite oxide (A), or also protects the surface of the composite oxide (B), thereby suppressing the side reaction of the electrolyte on the surface of the composite oxide (A, B) particles.
[0044] The M2 compound is an oxide, a hydroxide, or a carbonate. As specific examples of the M2 compound, SrO, CaO, Sr(OH)2, Ca(OH)2, SrCO3, CaCO3, etc. can be cited. Relative to the total molar number of metal elements other than Li constituting the composite oxide (A), the amount of the M2 compound is, for example, 0.05 to 0.5 mol% in terms of the metal element M2. The presence of the M2 compound can be confirmed by energy dispersive X-ray spectroscopy (TEM-EDX). In addition, the metal element M2 can be determined by using ICP emission spectrometry analysis on a solution obtained by dissolving the composite oxide (A) in fluoronitric acid.
[0045] The composite oxide (A) is manufactured, for example, through the following steps: a first step of obtaining a composite oxide containing Ni, a metal element M, etc.; a second step of mixing the composite oxide with a Li raw material to obtain a mixture; and a third step of calcining the mixture. In the case where an M2 compound is fixed to the particle surface of the composite oxide (A), a raw material containing the metal element M2 (hereinafter referred to as "M2 raw material") can be added in the second step. The composition, particle size, BET specific surface area, etc. of the composite oxide (A) and the M2 compound can be adjusted by controlling the mixing ratio of the raw materials, the calcination conditions in the third step, etc.
[0046] In the first step, for example, a solution of a metal salt containing a metal element such as Ni and a metal element M is stirred while an alkaline solution such as sodium hydroxide is added dropwise to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing the metal element. Thereafter, the composite hydroxide is calcined to obtain a composite oxide containing Ni, a metal element M, etc. The calcination temperature is not particularly limited, but as an example, is 300 to 600°C.
[0047] In the second step, the composite oxide obtained in the first step, the Li raw material, and the M2 raw material as required are mixed to obtain a mixture. As an example of the Li raw material, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be mentioned. As an example of the M2 raw material, oxides, hydroxides, carbonates, nitrates, sulfates, etc. of M2 can be mentioned. The mixing ratio of the composite oxide obtained in the first step and the Li raw material is adjusted, for example, in a manner such that the molar ratio of the metal element other than Li: Li is 1:0.98 to 1:1.22. In addition, the mixing ratio of the composite oxide and the M2 raw material is adjusted, for example, in a manner such that the molar ratio of the metal element other than Li: M2 is 1:0.0005 to 1:0.005.
[0048] In the third step, the mixture obtained by the second step is fired at a specified temperature and time to obtain a fired product. The firing of the mixture is carried out, for example, by multi-stage firing, which includes: a first firing step, firing in a firing furnace, under an oxygen flow, to a first set temperature of 450°C or more and 680°C or less at a first heating rate; a second firing step, after the first firing step, firing in a firing furnace, under an oxygen flow, to a second set temperature of more than 680°C and less than 800°C at a second heating rate. The first heating rate is 1.5 to 5.5°C / min, and the second heating rate is slower than the first heating rate, and can be 0.1 to 3.5°C / min. It should be noted that multiple heating rates can be set in each firing step.
[0049] The holding time of the first set temperature in the first firing step is, for example, 0 to 5 hours, or 0 to 3 hours. It should be noted that the holding time of the set temperature refers to the time for maintaining the set temperature after reaching the set temperature. The holding time of the second set temperature in the second firing step is, for example, 1 to 10 hours, or 1 to 5 hours. The mixture is fired in an oxygen gas flow with an oxygen concentration of 60% or more, and the firing furnace is heated every 10 cm. 3 The flow rate of the oxygen gas stream can be 0.2 to 4 mL / min, and the flow rate of the oxygen gas stream can be 0.3 L / min or more per 1 kg of the mixture. The calcined product can be washed with water, dehydrated, and dried to remove impurities.
[0050] It should be noted that M2 raw material may not be added in the second process, but added in the third process, during the washing of the fired product or during drying. For example, in a vacuum atmosphere, heat treatment is carried out at 150 to 400 °C for 0.5 to 15 hours, so that the M2 compound is fixed on the surface of the particles of the composite oxide (A).
[0051] [Second lithium transition metal composite oxide (composite oxide (B))]
[0052] As described above, the composite oxide (B) has the general formula Li a Ni 2-a-b Me b O2 (where 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, and Me is at least one metal element other than Li and Ni). The content of the metal element Me is preferably less than the contents of Li and Ni. For example, it is less than 10 mol% or less than 5 mol% relative to the total molar amount of the metal elements. As an example of the metal element Me, at least one selected from Cu, Sr, Ca, Nb, Si, and Al can be cited.
[0053] For the composite oxide (B), there is no release or absorption of Li due to charge and discharge, and its composition does not change. When such a composite oxide (B) is used in combination with the composite oxide (A), the cycle characteristics of the battery are specifically improved. In the composite oxide (B), a plurality of composite oxides with similar compositions may be contained. In the above general formula, a is more preferably 0.1 ≤ a ≤ 0.5, or 0.2 ≤ a ≤ 0.4. When a is within this range, the cycle characteristics are more effectively improved. It should be noted that the composition of the composite oxide (B) can be identified by an X-ray diffraction pattern or analyzed by using ICP emission spectroscopy.
[0054] The composite oxide (B) is, for example, a composite oxide having at least one diffraction peak, and the diffraction peak has a peak top at a diffraction angle (2θ) of 21.40° to 21.65° in synchrotron radiation X-ray diffraction (light energy 16 keV). It is sufficient that the diffraction peak has a peak top within the range of 2θ = 21.40° to 21.65°, and it can be a broad peak where the whole peak does not exist within this range. In the X-ray diffraction pattern of the composite oxide (B), for example, there is one peak top within the range of 2θ = 21.40° to 21.65°.
[0055] For the X-ray diffraction pattern of the composite oxide (B), it is obtained by powder X-ray diffraction method carried out under the following conditions using a synchrotron radiation facility (optical path BL5S2 of the Aichi Synchrotron Radiation Center).
[0056] Light energy: 16 keV
[0057] Scanning range: 10~90°
[0058] Analytical optical system: Debye-Scherrer type
[0059] The obtained data were used to search for peaks and identify the composite oxide (B) using identification and analysis software PDXL (manufactured by Rigaku Corporation).
[0060] In the measurement performed with the above device, NiO has a peak at 21.36°, and as a in the above general formula increases, the peak moves to the high angle side. When a in the above general formula is within the above range, there is a main peak at 21.40° to 21.65°. By comparing with the JCPDS card containing other peaks, the composite oxide (B) can be identified.
[0061] The composite oxide (B) is, for example, a particle having a smaller particle size than the composite oxide (A), and is a secondary particle formed by the aggregation of multiple primary particles. An example of D50 of the composite oxide (B) is 1 to 15 μm, or 1 to 10 μm, or 2 to 7 μm. The D50 of the composite oxide (B) may be less than 1 / 2 of the D50 of the composite oxide (A), preferably 1 / 5 to 1 / 2 of the D50 of the composite oxide (A), or 1 / 3 to 1 / 2 of the D50 of the composite oxide (A). By making the particle size of the composite oxide (B) smaller than the particle size of the composite oxide (A), a good contact state of each particle can be obtained, thereby enhancing the effect of improving the cycle characteristics. In addition, the BET specific surface area of the composite oxide (B) is, for example, 0.5 to 2.5 m 2 / g.
[0062] For the composite oxide (B), in the positive electrode mixture layer 31, for example, it exists in a state surrounded by a plurality of composite oxides (A). In addition, the particle surfaces of the composite oxides (A, B) are in contact with each other. In this case, it is believed that the interaction between the composite oxides (A, B) is more effectively manifested, thereby improving the cycle characteristics. It should be noted that the composite oxide (B) is not limited to intentionally added substances, and can be mixed as a by-product of the composite oxide (A) or an impurity of other positive electrode materials.
[0063] The composite oxide (B) is manufactured, for example, by the following steps: a first step of mixing a predetermined amount of a Li raw material and a Ni raw material to obtain a mixture; a second step of calcining the mixture at 500 to 800° C. for 10 to 30 hours. In the first step, the raw materials can be crushed as needed, or a raw material containing the metal element Me can be added within the range in which the X-ray diffraction pattern of the composite oxide (B) satisfies the above conditions. In addition, in the second step, the mixture can be formed into a pellet shape and then calcined, or it can be crushed after calcining. The calcination in the second step is carried out, for example, in the air or in an oxygen atmosphere.
[0064] As an example of the Li raw material, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be cited. As an example of the Ni raw material, NiO, Ni(OH)2, NiCO3, NiSO4, Ni(NO3)2, etc. can be cited. The mixing ratio of the Li raw material and the Ni raw material is adjusted such that the X-ray diffraction pattern of the composite oxide (B) satisfies the above conditions and such that a in the above general formula satisfies the condition of 0 < a ≤ 0.5.
[0065] [Conductive agent]
[0066] As described above, the positive electrode mixture layer 31 contains a conductive agent. The conductive agent forms a good conductive path in the positive electrode mixture layer 31, contributing to the reduction of the resistance of the positive electrode mixture layer 31. In the positive electrode mixture layer 31, carbon nanotubes (CNTs) are contained as the conductive agent. In addition, in the positive electrode mixture layer 31, granular conductive agents such as CNTs and carbon black, acetylene black, Ketjen black, graphite, etc., vapor-grown carbon fibers (VGCFs), electrospun carbon fibers, polyacrylonitrile (PAN)-based carbon fibers, pitch-based carbon fibers, graphene, etc. may be contained as the conductive agent.
[0067] It is considered that CNTs form a good conductive path in the positive electrode mixture layer 31, connect the particles of the composite oxides (A, B) to each other, improve the surface protection effect brought by the composite oxide (B), and specifically improve the cycle characteristics of the battery by coexisting the composite oxide (B) and CNTs. The content of CNTs is, for example, 0.01 to 5% by mass, more preferably 0.04 to 2% by mass, or 0.06 to 0.8% by mass, relative to the total mass of the positive electrode mixture layer 31. When the content of CNTs is within this range, the cycle characteristics can be efficiently improved. In the positive electrode mixture layer 31, only CNTs may be contained as the conductive agent.
[0068] The CNTs can be either single-walled CNTs (SWCNTs) or multi-walled CNTs (MWCNTs). In addition, as the MWCNTs, for example, CNTs having a tubular film structure in which graphene sheets formed of carbon hexagons are parallelly curled with respect to the fiber axis, CNTs having a platelet structure in which graphene sheets formed of carbon hexagons are arranged perpendicularly to the fiber axis, CNTs having a herringbone structure in which graphene sheets formed of carbon hexagons are curled at an inclined angle with respect to the fiber axis, etc. can be used. Two or more kinds of CNTs may also be added to the positive electrode mixture layer 31.
[0069] The average diameter of CNT is, for example, less than 50 nm, preferably less than 40 nm, more preferably less than 25 nm, or less than 20 nm. The lower limit of the average diameter of CNT is not particularly limited, and as an example, is 1 nm or 5 nm. An example of a suitable range of the average diameter of CNT is 1 to 20 nm, or 5 to 20 nm. When the average diameter of CNT is within this range, the improvement effect of the cycle characteristics is improved compared to using CNTs with an average diameter outside this range.
[0070] The average fiber length of CNT is, for example, 0.5 μm or more, preferably 0.7 μm or more, more preferably 0.8 μm or more, or 1 μm or more. The upper limit of the average fiber length of CNT is not particularly limited, but as an example, it is 10 μm or 5 μm. An example of a suitable range of the average fiber length of CNT is 1 to 10 μm, or 1 to 5 μm. When the average fiber length of CNT is within this range, the improvement effect of the cycle characteristics is improved compared to using CNT with an average fiber length outside this range.
[0071] The average fiber length of CNT is shorter than the length corresponding to the composite oxide (B) D50, for example. It should be noted that the average diameter of CNT is obtained from the surface transmission electron microscope (TEM) image of the positive electrode mixture layer 31, and the average fiber length is obtained by selecting 100 CNTs from the cross-sectional SEM image of the positive electrode mixture layer 31, measuring the diameter and fiber length, and averaging the measured values.
[0072] <Negative electrode>
[0073] like Figure 2 As shown, the negative electrode 12 has a negative electrode core 40 and a negative electrode mixture layer 41 formed on at least one surface of the negative electrode core 40. The negative electrode core 40 can use a foil of a metal that is stable in the potential range of the negative electrode, such as copper or copper alloy, or a thin film that arranges the metal on the surface. The negative electrode mixture layer 41 contains a negative electrode active material and a binder, and it is preferred to form it on both surfaces of the negative electrode core 40. In addition, a conductive agent such as CNT can be added to the negative electrode mixture layer 41. The negative electrode 12 can be manufactured by coating a negative electrode mixture slurry containing a negative electrode active material and a binder on the negative electrode core 40, compressing the coating after drying, and forming the negative electrode mixture layer 41 on both surfaces of the negative electrode core 40.
[0074] The negative electrode mixture layer 41 includes, as the negative electrode active material, a carbon-based active material, at least one selected from Si, Sn, Sb, Mg, and Ge (hereinafter referred to as "metal element M3"), and at least one of an M3 compound containing the metal element M3. The content of the metal element M3 and the M3 compound is, for example, 0.5 to 30% by mass, preferably 1 to 15% by mass, relative to the total mass of the negative electrode active material.
[0075] A metal element M3 can be added to the negative electrode mixture layer 41, but it is preferably to add an M3 compound. As an example of the M3 compound, SiC, SnO2, a first silicon material (SiO) containing a silicon oxide phase and Si dispersed in the silicon oxide phase, a second silicon material (LSX) containing a lithium silicate phase and Si dispersed in the lithium silicate phase, a third silicon material (Si-C) containing a carbon phase and Si dispersed in the carbon phase, etc. can be cited. Among them, SiO, LSX or Si-C is preferred.
[0076] For carbon-based active materials, natural graphite such as flake graphite, massive artificial graphite, graphitized mesophase carbon microspheres and other artificial graphite can be used, for example. The content of the carbon-based active material (graphite) is, for example, 70 to 99.5% by mass, or 85 to 99% by mass, relative to the mass of the negative electrode active material. In addition, an example of the D50 of the carbon-based active material is 1 to 20 μm, or 2 to 15 μm. By using the carbon-based active material in combination with the M3 compound, good cycle characteristics can be maintained and high capacity can be achieved.
[0077] SiO and LSX are, for example, particles with a D50 smaller than that of graphite. An example of the D50 of SiO and LSX is 1 μm to 15 μm, or 3 μm to 10 μm. A conductive layer made of a material with high conductivity can be formed on the particle surface of SiO and LSX. An example of a suitable conductive layer is a carbon coating made of a carbon material. Considering the ensuring of conductivity and the diffusibility of lithium ions into the particle interior, the thickness of the conductive layer is preferably 1 to 200 nm, or 5 to 100 nm.
[0078] SiO has a particle structure in which fine Si particles are dispersed in a silicon oxide phase. Suitable SiO has an island structure in which fine Si particles are roughly uniformly dispersed in a matrix of amorphous silicon oxide, and is represented by the general formula SiOx (0 < x ≤ 2). The silicon oxide phase is composed of a collection of particles finer than the Si particles. From the viewpoint of balancing battery capacity and cycle characteristics, the content rate of the Si particles is preferably 35 to 75% by mass relative to the total mass of SiO.
[0079] The average particle diameter of the Si particles dispersed in the silicon oxide phase is, for example, 500 nm or less before charge and discharge, preferably 200 nm or less, or 50 nm or less. After charge and discharge, it is, for example, 400 nm or less, or 100 nm or less. For the average particle diameter of the Si particles, the particle cross-section of SiO is observed using SEM or transmission electron microscope (TEM), and it is obtained as the average value of the longest diameters of 100 Si particles.
[0080] LSX has a particulate structure with fine Si particles dispersed in a lithium silicate phase. Suitable LSX has an island structure in which fine Si particles are dispersed substantially uniformly in a matrix of lithium silicate. The lithium silicate phase is composed of an aggregate of particles finer than the Si particles. Similarly to the case of SiO, the content of Si particles is preferably 35 to 75% by mass relative to the total mass of LSX. In addition, the average particle diameter of the Si particles is, for example, 500 nm or less before charge and discharge, preferably 200 nm or less, or 50 nm or less.
[0081] The lithium silicate phase is preferably composed of a compound represented by the general formula Li 2z SiO (2+z) (0 < z < 2). That is, Li4SiO4 (Z = 2) is not contained in the lithium silicate phase. Li4SiO4 is an unstable compound and reacts with water to show alkalinity, so it may cause Si to deteriorate and lead to a decrease in charge and discharge capacity. From the viewpoints of stability, ease of production, lithium ion conductivity, etc., the lithium silicate phase preferably has Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2) as the main component. When Li2SiO3 or Li2Si2O5 is the main component, the content of this main component is preferably more than 50% by mass, more preferably 80% by mass or more, relative to the total mass of the lithium silicate phase.
[0082] Si-C has a carbon phase and silicon particles dispersed in the carbon phase. From the viewpoint of high capacity, etc., the content of silicon particles in suitable Si-C is preferably 30% by mass or more and 80% by mass or less, preferably 35% by mass or more and 75% by mass or less, more preferably 55% by mass or more and 70% by mass or less. The average particle diameter of suitable silicon particles is generally 500 nm or less before charge and discharge, preferably 200 nm or less, more preferably 100 nm or less. After charge and discharge, it is preferably 400 nm or less, more preferably 100 nm or less. The average particle diameter of the silicon particles is measured by observing the particle cross-section of Si-C using SEM or TEM, and specifically, it can be obtained as the average value of the longest diameters of 100 silicon particles.
[0083] For the binder contained in the negative electrode mixture layer 41, similar to the case of the positive electrode 11, a fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc. can be used, but styrene-butadiene rubber (SBR) is particularly preferably used. In addition, the negative electrode mixture layer 41 further preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use a combination of SBR, and CMC or its salt, PAA or its salt. The content of the binder is, for example, 0.1 to 5% by mass relative to the mass of the negative electrode active material.
[0084] <Separator>
[0085] As Figure 2As shown, the separator 13 has a porous substrate 50 and a surface layer 51 formed on the surface of the substrate 50 facing the positive electrode 11. The surface layer 51 is a layer containing inorganic particles and a binder. The surface layer 51 can be formed on both sides of the substrate 50, but from the perspective of high capacity, it is preferably formed only on a single side of the substrate 50 facing the positive electrode 11. The separator 13 is a porous sheet between the positive electrode 11 and the negative electrode 12 that prevents electrical contact between the two electrodes and has ion permeability and insulation. The porosity of the separator 13 is, for example, 30% to 70%. It should be noted that the porosity of the separator 13 is determined by the porosity of the substrate 50.
[0086] The substrate 50 is a porous sheet made of resin. The thickness of the substrate 50 is, for example, 5 to 50 μm, more preferably 10 to 30 μm. The resin constituting the substrate 50 is not particularly limited, but specific examples thereof include polyolefins such as polyethylene, polypropylene, copolymers of ethylene and α-olefins, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polyetheretherketone, polyimide, fluororesin, cellulose, and the like. The substrate 50 may have a single-layer structure or a laminated structure such as a three-layer structure of polyethylene / polypropylene / polyethylene.
[0087] The surface layer 51 is porous like the substrate 50 and has ion permeability and insulation. The thickness of the surface layer 51 is not particularly limited, but is preferably thinner than the thickness of the substrate 50, for example, 0.5 to 10 μm, preferably 1 to 6 μm. The surface layer 51 is in contact with the surface of the positive electrode mixture layer 31, and is preferably formed on approximately the entire area of one side of the substrate 50. The surface layer 51 is formed, for example, by applying a slurry containing inorganic particles and a binder to the entire surface of the substrate 50 and drying the coating.
[0088] The surface layer 51 is a layer with inorganic particles as the main component. Relative to the total mass of the surface layer 51, the content of inorganic particles is, for example, 70% by mass or more, preferably 80% by mass or more. The suitable range of the content of inorganic particles is 70 to 99% by mass, or 80 to 98% by mass, or 85 to 95% by mass. The surface layer 51 has the function of suppressing damage to the separator 13 caused by conductive foreign matter, deformation of the separator 13 during abnormal heating, etc. Furthermore, it is believed that the surface layer 51 in contact with the positive electrode 11 suppresses the side reaction of the electrolyte on the positive electrode 11 caused by the interaction with the composite oxide (B), and by providing the surface layer 51, the cycle characteristics and storage characteristics of the battery are specifically improved.
[0089] Examples of the inorganic particles included in the surface layer 51 include particles of metal oxides, metal nitrides, metal fluorides, metal carbides, metal hydroxides such as aluminum hydroxide (boehmite), magnesium hydroxide, metal carbonates such as calcium carbonate, magnesium carbonate, and barium carbonate, and metal sulfates such as calcium sulfate, magnesium sulfate, and barium sulfate. The inorganic particles may be used alone or in combination of two or more. The D50 of the inorganic particles is, for example, 0.01 to 10 μm, preferably 0.05 to 5 μm.
[0090] An example of a metal oxide is aluminum oxide (alumina), titanium oxide, magnesium oxide, zirconium oxide, nickel oxide, silicon oxide, manganese oxide, etc. An example of a metal nitride is titanium nitride, boron nitride, aluminum nitride, magnesium nitride, silicon nitride, etc. An example of a metal fluoride is aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, barium fluoride, etc. An example of a metal carbide is silicon carbide, boron carbide, titanium carbide, tungsten carbide, etc. From the viewpoint of improving cycle characteristics and storage characteristics, an example of a suitable inorganic particle is at least one selected from alumina, boehmite and barium sulfate.
[0091] There is no particular limitation on the binder contained in the surface layer 51 as long as it can fix the inorganic particles to each other and to the substrate 50 and has electrolyte resistance. For example, the same binder as used in the positive electrode mixture layer 31 and the negative electrode mixture layer 41 can be used. As specific examples, fluororesins such as PVdF and PTFE, PAN, acrylic resins, etc. can be cited. In addition, a resin with high heat resistance such as an aromatic amide resin can also be used. As an example of a suitable binder, at least one selected from an aromatic amide resin and an acrylic resin can be cited.
[0092] [Non-aqueous electrolyte]
[0093] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For the non-aqueous solvent, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof can be used. The non-aqueous solvent may contain a halogen substituted body in which at least a portion of the hydrogen of these solvents is substituted with a halogen atom such as fluorine. As the halogen substituted body, fluorinated cyclic carbonates such as fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP) and the like can be cited. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte, but may also be a solid electrolyte.
[0094] In a non-aqueous electrolyte, a sulfonylimide salt is contained as an electrolyte salt. In a non-aqueous electrolyte secondary battery 10 including a positive electrode 11 containing a composite oxide (A, B), by adding a sulfonylimide salt to the non-aqueous electrolyte, it is considered that a good protective film is formed on the surface of the particles of the positive electrode active material, suppressing side reactions of the electrolyte on the particle surface, and specifically improving the cycle characteristics. The concentration of the sulfonylimide salt is preferably 0.05 to 2.5 mol / L, more preferably 0.1 to 2.0 mol / L, or 0.1 to 1.5 mol / L. When the content of the sulfonylimide salt is within this range, the cycle characteristics can be improved more effectively.
[0095] The sulfonylimide salt added to the non-aqueous electrolyte is preferably lithium sulfonylimide. Examples of lithium sulfonylimide include lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide, lithium bis(nonafluorobutanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide (LIBETI), etc. Among them, at least one lithium sulfonylimide selected from LiFSI and lithium bis(trifluoromethanesulfonyl)imide is preferred. The sulfonylimide salt can be used alone or in combination of two or more.
[0096] In the non-aqueous electrolyte, other lithium salts can further be contained. Examples of other lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), etc. Among them, from the viewpoints of ionic conductivity, electrochemical stability, etc., LiPF6 is preferably used.
[0097] In the non-aqueous electrolyte, lithium sulfonylimide and a second lithium salt preferably coexist. In this case, a combination of LiFSI and LiPF6 is particularly preferred. When the second lithium salt is contained, the concentration of the lithium sulfonylimide is also adjusted to the above range, for example. As a specific example, the concentration of the lithium sulfonylimide is set to 0.1 to 1.5 mol / L, and the total concentration of the lithium salts is set to 1.5 to 2.5 mol / L. The concentration of the lithium sulfonylimide is, for example, 30 to 70% of the concentration of the lithium salts contained in the non-aqueous electrolyte.
[0098] In addition, the non-aqueous electrolyte may contain additives such as vinylene carbonate (VC), ethylene sulfite (ES), cyclohexylbenzene (CHB), o-terphenyl (OTP), and propane sultone compounds. Among them, VC is preferably added from the viewpoint of high capacity. The concentration of the additive is not particularly limited, and is, for example, 0.1 to 5% by mass.
[0099] As mentioned above, esters and ethers can be used as non-aqueous solvents. As examples of esters, cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, cyclic carboxylates such as gamma-butyrolactone (GBL), gamma-valerolactone (GVL), methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), chain carboxylates such as ethyl propionate (EP), etc. can be enumerated.
[0100] Examples of ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ethers, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl ether, and the like. Alkenyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether and other chain ethers, etc.
[0101] (Variation Example)
[0102] On the particle surface of the composite oxide (A), instead of the compound containing the metal element M2, other compounds such as compounds containing lanthanide elements may be fixed. Alternatively, on the particle surface of the composite oxide (A), there may be substantially no fixed substance. In addition, a composite oxide (B) with a small particle size may be fixed on the particle surface of the composite oxide (A).
[0103] The negative electrode mixture layer may not contain the metal element M3 and the M3 compound, and may contain only a carbon-based active material such as graphite as the negative electrode active material.
[0104] The separator may also be a porous sheet without a surface layer mainly composed of inorganic particles. Alternatively, a surface layer mainly composed of inorganic particles may be provided on the surface of the positive electrode mixture layer. In addition, the non-aqueous electrolyte may not contain a sulfonimide salt, and may contain only LiPF6 as a lithium salt.
[0105] Example
[0106] The present invention will be further described below by way of examples, but the present invention is not limited to these examples.
[0107] <Example 1>
[0108] [Synthesis of composite oxide (A1)]
[0109] The [Ni 0.91 Co 0.04 Al 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a composite oxide (Ni 0.91 Co 0.04 Al 0.05 O2) (Step 1). Then, lithium hydroxide (LiOH) and the composite oxide are mixed in such a manner that the molar ratio of Li to the total amount of Ni, Co, and Al is 1.02:1 to obtain a mixture. The mixture is placed under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and 5 L / min per kg of the mixture), and then calcined from room temperature to 650°C at a rate of 2°C / min, and then calcined from 650°C to 720°C at a rate of 0.5°C / min. The calcined product was washed with water to remove impurities, thereby obtaining a composite oxide (A1).
[0110] The results of ICP analysis showed that the composition of the composite oxide (A1) was LiNi 0.91 Co 0.04 Al 0.05 O2. In addition, the crystal structure of the first lithium transition metal composite oxide was identified as belonging to the space group R-3m by X-ray diffraction. The D50 of the composite oxide (A1) measured using MT3000II manufactured by Microtrac BEL with water as a dispersion medium was 10 μm.
[0111] [Synthesis of composite oxide (B1)]
[0112] Li2O and NiO were weighed so that the molar ratio of Li to Ni was 0.3:1.7, and they were crushed and mixed to prepare a mixture. Next, the mixture was calcined at 650°C for 20 hours in an oxygen atmosphere, and further crushed to obtain a composite oxide (B1). When the powder X-ray diffraction measurement of the composite oxide (B1) was carried out using the above-mentioned radiation light facility, a peak with a peak top at 21.48° was confirmed in the range of 2θ=21.40°~21.65° of the obtained X-ray diffraction pattern. In addition, by comparing with the JCPDS card containing other peaks, the composition of the composite oxide (B1) was confirmed to be Li 0.3 Ni 1.7 O2. D50 of the composite oxide (B1) measured using MT3000II manufactured by Microtrac BEL Co., Ltd. with water as a dispersion medium was 5 μm.
[0113] [Production of positive electrode]
[0114] A composite oxide (A1, B1) mixed in a mass ratio of 99.5:0.5 is used as a positive electrode active material. The positive electrode active material, CNT (a) with an average diameter of 10 nm and an average fiber length of 0.5 μm, and polyvinylidene fluoride (PVdF) are mixed in a solid content mass ratio of 96.5:0.5:3, and after adding an appropriate amount of N-methylpyrrolidone (NMP), they are kneaded to prepare a positive electrode mixture slurry. The positive electrode mixture slurry is applied to a positive electrode core made of aluminum foil, and after the coating film is dried, the coating film is rolled using a rolling roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that a portion of the positive electrode is provided with an exposed portion that exposes the surface of the positive electrode collector.
[0115] [Production of negative electrode]
[0116] Graphite (negative electrode active material), a dispersant of styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC-Na) were mixed at a solid content mass ratio of 98:1:1, and water was used as a dispersion medium to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of a negative electrode core made of copper foil, and after the coating was dried and compressed, it was cut into a specified electrode size to produce a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core.
[0117] [Preparation of non-aqueous electrolyte]
[0118] LiPF6 was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3:7 (25°C, 1 atmosphere) to prepare a non-aqueous electrolyte.
[0119] [Production of test battery cells]
[0120] An aluminum lead was installed at the exposed portion of the positive electrode, a nickel lead was installed at a predetermined position of the negative electrode, and the positive electrode and the negative electrode were placed opposite each other via a polyolefin separator to produce an electrode body. The electrode body was housed in an outer casing, the nonaqueous electrolyte was injected, and the opening of the outer casing was sealed to obtain a test battery cell.
[0121] <Example 2>
[0122] In the production of the positive electrode, a test cell was produced in the same manner as in Example 1 except that CNT (b) having an average diameter of 10 nm and an average fiber length of 1.0 μm was used instead of CNT (a).
[0123] <Example 3>
[0124] In the production of the positive electrode, a test cell was produced in the same manner as in Example 1 except that CNT(c) having an average diameter of 20 nm and an average fiber length of 1.5 μm was used instead of CNT(a).
[0125] <Example 4>
[0126] In the production of the positive electrode, a test cell was produced in the same manner as in Example 1, except that CNT(d) having an average diameter of 37 nm and an average fiber length of 1.5 μm was used instead of CNT(a).
[0127] <Example 5>
[0128] A test cell was prepared in the same manner as in Example 1 except that Li2O and NiO were mixed so that the molar ratio of Li to Ni was 0.2:1.8 to synthesize a composite oxide (B2).
[0129] <Example 6>
[0130] A test cell was produced in the same manner as in Example 1 except that Li 2 O and NiO were mixed so that the molar ratio of Li to Ni was 0.5:1.5 to synthesize a composite oxide (B3).
[0131] <Comparative Example 1>
[0132] In the preparation of the positive electrode, the composite oxide (B1) is not used, and AB is used instead of CNT (a). The positive electrode active material (composite oxide (A1)), acetylene black (AB), and PVdF are mixed in a solid content mass ratio of 96:1:3. Except for this, the test battery cell is prepared in the same manner as Example 1.
[0133] <Comparative Example 2>
[0134] A test cell was prepared in the same manner as in Example 1 except that AB was used instead of CNT (a) in the preparation of the positive electrode, and the positive electrode active material, AB, and PVdF were mixed at a solid content mass ratio of 96:1:3.
[0135] <Comparative Example 3>
[0136] A test cell was produced in the same manner as in Example 1 except that the composite oxide (B1) was not used in the production of the positive electrode.
[0137] <Comparative Example 4>
[0138] A test cell was produced in the same manner as in Example 1 except that the following composite oxide (B10) was used instead of the composite oxide (B1) in the production of the positive electrode.
[0139] [Synthesis of composite oxide (B10)]
[0140] Li2O and NiO were weighed so that the molar ratio of Li to Ni was 0.7:1.3, and these were crushed and mixed to prepare a mixture. Next, the mixture was calcined at 650°C for 20 hours in an oxygen atmosphere and further crushed to obtain a composite oxide (B10).
[0141] The charge-discharge cycle characteristics of each test battery cell of the example and the comparative example were evaluated by the following method. The evaluation results are shown in Table 1 together with the configuration of the positive electrode.
[0142] [Evaluation of Cycle Characteristics (Capacity Retention Rate)]
[0143] The test battery cell was charged at a constant current of 0.3C until the battery voltage reached 4.3V, and then charged at a constant voltage of 4.3V until the current value reached 0.02C under a temperature environment of 25°C. Thereafter, the battery was discharged at a constant current of 0.05C until the battery voltage reached 2.5V. The charge and discharge were repeated for 30 cycles, and the capacity retention rate after 30 cycles was calculated based on the following formula. The capacity retention rates shown in Table 1 are relative values with respect to the capacity retention rate of the test battery cell of Comparative Example 1 as the reference (100).
[0144] Capacity retention rate = (discharge capacity at the 30th cycle / discharge capacity at the 1st cycle) × 100
[0145] [Table 1]
[0146]
[0147] As can be understood from the results shown in Table 1, the capacity retention rates of the test battery cells of the examples are all higher and the cycling characteristics are all excellent compared with those of the test battery cells of the comparative examples. That is, when using a positive electrode containing the composite oxide (A1) and the composite oxides (B1 to B3) represented by the general formula Li a Ni 2-a- b Me b O2 (where 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, and Me is at least one metal element other than Li and Ni) and CNT, a specific improvement in the cycling characteristics can be seen.
[0148] When using the composite oxide (A1) alone as the positive electrode active material (Comparative Examples 1 and 3), when not using CNT as the conductive agent (Comparative Examples 1 and 2), and when using a composite oxide (B10) that does not satisfy the conditions of the above general formula instead of the composite oxides (B1 to B3) (Comparative Example 4), the improvement effect of the cycling characteristics as in the examples cannot be obtained.
[0149] Explanation of reference numerals
[0150] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer can, 17 Sealing body, 18, 19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Groove portion, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating member, 26 Upper valve body, 27 Cover body, 28 Gasket, 30 Positive electrode core, 31 Positive electrode mixture layer, 40 Negative electrode core, 41 Negative electrode mixture layer, 50 Substrate, 51 Surface layer
Claims
1. A positive electrode for a non-aqueous electrolyte secondary battery, which is a positive electrode for a non-aqueous electrolyte secondary battery having a positive electrode mixture layer, wherein: The positive electrode mixture layer comprises: General formula Li x Ni 1-y-z Co y M z The first lithium transition metal composite oxide represented by O2, where 0.8 ≤ x ≤ 1.2, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.5, and M is at least one metal element other than Li, Ni, and Co; General formula Li a Ni 2-a-b Me b The second lithium transition metal composite oxide represented by O2, where 0 < a ≤ 0.5, 0 ≤ b ≤ 0.5, Me is at least one metal element other than Li and Ni; and Carbon nanotubes, The content of the second lithium transition metal composite oxide is 0.1 to 10% by mass relative to the total mass of the positive electrode mixture layer. The second lithium transition metal composite oxide is a composite oxide having at least one diffraction peak having a peak top at a diffraction angle 2θ of 21.40° to 21.65° in synchrotron radiation X-ray diffraction at a light energy of 16 KeV.
2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The content of the carbon nanotubes is 0.01 to 5% by mass relative to the total mass of the positive electrode mixture layer.
3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The average diameter of the carbon nanotubes is less than 20 nm, and the average fiber length is more than 1 μm.
4. A non-aqueous electrolyte secondary battery comprising: A positive electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, Negative electrode, and Non-aqueous electrolytes.
5. The nonaqueous electrolyte secondary battery according to claim 4, wherein The negative electrode contains a carbon-based active material and a second active material as negative electrode active materials, the second active material contains at least one of a metal element and a compound containing the metal element, and the metal element is selected from at least one of Si, Sn, Sb, Mg and Ge. The content of the second active material is 1 to 15% by mass relative to the total mass of the negative electrode active material.
Citation Information
Patent Citations
Internal combustion engine electronic ignition timing controller
JP1978059140A
Positive plate active material and nonaqyeous electrolyte secondary cell using same
US20040076882A1
Lithium ion secondary battery
US20190280284A1